Ariosophic Whiteness in the Early Norwegian Black Metal Videos - Kärki, Kimi (Routledge, 2025)
Many of the negative and nocturnal aspects of the Scandinavian cultural heritage have been explored by means of bringing perhaps the most notorious of all music scenes, black metal, in the music video format. Common traits of black metal include fast tempos, a shrieking vocal style, heavily distorted, often trebly guitars played with tremolo picking, raw low-fidelity recording, unconventional song structures, transgressive and often provocative lyrics, and an emphasis on atmosphere. Black metal musicians often appear in corpse paint and adopt pseudonyms. Some of these groups portray the Nordic region as an originally racially pure, historically white, pagan region, that has a special warrior ethos, and a heroic mythological, mostly Viking, past. The combination of myths and darkness creates an inward-looking, cultic, hypnotic, and ritualistic mood to the music. In my chapter I analyse early black metal music videos in their 1990s cultural context. I will start my analysis from Richard Dyer's concept of “Whiteness,” and combine that to cultural historical contextualisation of Nordic Ariosophy and esoteric pseudoscience. I am particularly focusing on two videos, Burzum's “Dunkelheit” and Immortal's “The Call of the Wintermoon.” Clearly the first few videos that surfaced became influential for the development of the whole black metal multimodal aesthetic.
Keywords: musiikkivideot; black metal; estetiikka